Effects of raloxifene, hormone therapy, and soy isoflavone on serum high-sensitive C-reactive protein in postmenopausal women - Yildiz, MF; Kumru, S; Godekmerdan, A; Kutlu, S (Wiley, 2005)
Objective: To compare the effects of raloxifene, estradiol valerate plus dienogest, and soy isoflavones (genistein) on serum concentrations of high-sensitive C-reactive protein in healthy postmenopausal women. Methods: The 80 healthy postmenopausal women enrolled in the study were randomly allocated to receive 60 mg of raloxifene, 2 mg of estradiol valerate plus dienogest, 40 mg of genistein, or placebo (n = 20 in each group). Blood samples were collected at the start of the study and at 3 and 6 months. Lipid profile was also determined. Results: Only the group receiving estradiol valerate plus dienogest showed an increase in serum Levels of high-sensitive C-reactive protein compared with baseline values and values in the control and other groups. All 3 treatments resulted in an increase in high-density lipoprotein cholesterol levels and a decrease in total, tow-density, and very-low-density lipoprotein cholesterol levels. Conclusions: Estradiol valerate plus dienogest, but not raloxifene and genistein, increase serum high-sensitive C-reactive protein levels. All 3 treatments, however, have an estrogen-like effect on serum lipid profile. (c) 2005 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: hormone therapy; estradiol valerate; dienogest; raloxifene; soy isoflavones; high-sensitive C-reactive protein